2016
DOI: 10.1177/1060028016655425
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Mold

Abstract: Diagnosis of mucormycosis is typically difficult to make based on imaging studies, sputum culture, bronchoalveolar lavage culture, or needle aspirate. Surgical debridement prior to dissemination of infection improves clinical outcomes. Surgery combined with early, high-dose systemic antifungal therapy yields greater than a 1.5-fold increase in survival rates. The Mucorales are inherently resistant to most widely used antifungal agents. Amphotericin B is appropriate for empirical therapy, whereas posaconazole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 75 publications
(80 reference statements)
0
69
1
Order By: Relevance
“…The overall survival is 92% in patients receiving posaconazole therapy, its higher than those receiving amphotericin B. Recent studies also have shown overall success rates of 60–70% with posaconazole as salvage therapy for zygomycetes infection [17, 18]. These encouraging data suggest that posaconazole may represent a prospective drug against mucormycosis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival is 92% in patients receiving posaconazole therapy, its higher than those receiving amphotericin B. Recent studies also have shown overall success rates of 60–70% with posaconazole as salvage therapy for zygomycetes infection [17, 18]. These encouraging data suggest that posaconazole may represent a prospective drug against mucormycosis.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this otherwise immunocompetent patient developed mucormycosis in the context of impaired glucose tolerance which was triggered by steroid use. Both hyperglycaemia and glucocorticoid use represent well-established risk factors for mucormycosis, probably due to impaired chemotaxis and neutrophil fungicidal activity and macrophage function respectively [1], [2], [6]. Once identified, aggressive surgical management as well as a multi-disciplinary approach has been shown to reduce mortality [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis is a relatively rare infection caused by ubiquitous fungi of the phylum Zygomycota, of which Rhizopus arrhizus is the most commonly isolated pathogen [1], [2]. It has an extremely high mortality rate which varies with the degree of immunosuppression but remains over 50% for rhino-orbital-cerebral disease [1], [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetes mellitus (DM) have markedly increased incidence of invasive mucormycosis. Despite the advancement of new antifungal drugs and combination therapies, the management of mucormycosis is still challenging (1,2). Here we presented the two cases of mucormycosis with a history of diabetic ketoacidosis.…”
Section: Introductionmentioning
confidence: 99%